Serpent (Ship) certification - Serpent (Ship)
Certification issued by the French customs office in Guadalupe to a vessel engaged in the grain and sugar trade between Baltimore, Md., and Basse-Terre, Guadalupe.
Collection material in French.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Customs administration -- Guadalupe; Grain trade -- Guadalupe -- Basse-Terre.; Grain trade -- Maryland -- Baltimore; Ship's papers -- 19th century; Sugar trade -- Guadalupe -- Basse-Terre.; Sugar trade -- Maryland -- Baltimore; France -- Colonies -- America